Internal consistency and reliability of the Swiss-French translation of the venous leg ulcer self efficacy tool (VeLUSET). Issue 12 (8th December 2019) - Probst, Sebastian; Turcotte, Mathieu; Buehrer Skinner, Monika
Abstract : Objective: This study was conducted to assess the psychometric properties of the translated and adapted Venous Leg Ulcer Self Efficacy Tool (VeLUSET) in the new cultural context. Design: Validation study Setting: Three outpatient clinics in Western Switzerland. Participants: 32 consecutive persons with venous leg ulcers (VLU). Main outcome measures: To determine the internal consistency and reliability of the VeLUSET for use in a Swiss-French speaking venous leg ulcer population. Results: Overall, the Cronbach alpha for the VeLUSET-FR was 0.96 (95% CI 0.93 to 0.98) on test and retest. Lin's concordance correlation coefficient of test and retest scores was 0.93 (95% CI 0.86 to 0.96). Conclusion: The results indicate that the VeLUSET-FR is a valid and reliable instrument for measuring self-efficacy among Swiss-French persons affected by a venous leg ulcer. Our findings show that the psychometric properties are similar to those of the original tool. Therefore, we suggest that the VeLUSET-FR can be effectively used for measuring self-efficacy in Swiss-French persons with VLU.